1995
DOI: 10.1002/mrd.1080410209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microinjection time during postfertilization S‐phase on bovine embryonic development

Abstract: Microinjection into bovine zygotes was performed to evaluate the effects of the timing of injection during the phase of DNA replication on the subsequent in vitro development of embryos and expression of injected chicken beta-actin promoter-lac Z gene construct. The period of DNA replication of bovine zygotes, determined by 3H-thymidine incorporation, begins between 12 hr and 13 hr postinsemination (hpi) of in vitro matured oocytes, reaches a maximum from 17 hpi to 19 hpi, and is complete by 21-22 hpi. Aphidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 70 publications
2
11
3
Order By: Relevance
“…This is not in accordance with Gagné et al [16], who observed similar development rates after aphidicolin treatments but mentioned only the morula rates. When oocytes were fertilized by high-fertility sperm, the timing of DNA replication after a short aphidicolin exposure mimics that of oocytes fertilized by low-fertility sperm without aphidicolin exposure.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This is not in accordance with Gagné et al [16], who observed similar development rates after aphidicolin treatments but mentioned only the morula rates. When oocytes were fertilized by high-fertility sperm, the timing of DNA replication after a short aphidicolin exposure mimics that of oocytes fertilized by low-fertility sperm without aphidicolin exposure.…”
Section: Discussionsupporting
confidence: 69%
“…The paternal influence on the onset of the S-phase was exerted simultaneously on both pronuclei and not only on the paternal pronucleus; this was not evidenced in the study of Eid et al [15]. Thereafter both pronuclei of a zygote had the same duration of DNA replication, in agreement with Gagné et al [16].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Bovine embryos transfected with reporter genes at the 1-cell stage express detectable amounts of reporter gene protein only after 42 h of culture around the 4-to 8-cell stage or later. In those experiments, reporter protein was also detected in arrested 1-cell embryos at this time [72,73].…”
Section: Discussionmentioning
confidence: 98%
“…Bovine embryos transfected with reporter genes at the 1-cell stage by pronuclear injection or retroviral transfer only express detectable amounts of reporter gene product following 42 hr of culture around the 4-to 8-cell stage or later, with product also detected in arrested 1-cell embryos at this time (Gagne et al, 1995;Kubisch et al, 1997). Temporal control of transcriptional permissiveness is also apparent in other species but appears to begin as early as the G2 phase of the first cell cycle in the mouse and rabbit (Vernet et al, 1992;Ram and Schultz, 1993;Christians et al, 1994;Nothias et al, 1996).…”
Section: Zygotic Gene Activationmentioning
confidence: 99%